Reproductive aspects of Oreochromis niloticus (Perciformes: Cichlidae) at Coatetelco lake, Morelos, Mexico - Gómez-Márquez, J L (2003)
Sex ratio, size at maturity, maturity stages, fecundity and egg diameter of Oreochromis niloticus from Coatetelco Lake, Morelos State, Mexico, were studied from January to December 1993. Sex ratio (male:female) was approximately 1:1.02. Length at maturity was 117 mm (males) and 120 mm (females). The fecundity ranged between 104 and 709 eggs, with egg diameter from 1 000 to 3 000 μm. The gonadosomatic and hepatosomatic index indicate that the species breeds during summer and winter.